Social media, digital history and women repression memory under Franco’ s regime. - Egido, Ángeles; Eiroa, Matilde (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
In recent years has advanced greatly in qualitative and quantitative studies about women repression during the Franco regime. In addition to the publication of several testimonies, there are rigorous research on the Francoist prisons for women, and novels, films and documentaries. Along with these new scenarios of diffusion, the digital environment currently sets a field where also express and disseminate content of this phenomenon of our most traumatic past. Within this framework, this paper proposes a comparative perspective among the state of arts with the presence of women prosecution in social platforms in order to verify the treatment conferred in the context of digital expressions of the Francoist repression.
Keywords: women repression; Franco's repression; digital hsitory; network stories